Effects of ketosis in mitochondrial myopathy: potential benefits of a mitotoxic diet. Issue 11 (11th October 2016) - Pitceathly, Robert DS; Viscomi, Carlo
Abstract : The field of mitochondrial medicine is rapidly transitioning from preclinical observation to clinical application. Translation of promising data obtained in mouse models is not always straight‐forward, however. Building on their own work showing that a ketogenic diet induces mitochondrial biogenesis and delays the onset of disease in the Deletor mouse, Ahola et al administered modified Atkins diet (mAD) to five patients with mitochondrial myopathy caused by mitochondrial DNA deletions (Ahola et al, 2016 ). Surprisingly, mAD did not induce mitochondrial biogenesis in patients, but rather triggered the progressive damage of muscle cells, particularly those with impaired respiratory chain activity (the ragged‐red fibres). The subsequent extensive characterisation of the metabolic and molecular profile changes observed in patients and healthy controls provides a significant advance towards understanding the feasibility of dietary modification as a treatment strategy for mitochondrial diseases. Abstract : Pitceathly and Viscomi comment on a new report by Anu Suomalainen's team showing that a ketogenic modified Atkins diet induces muscle damage, especially of ragged‐red fibres, in human mitochondrial myopathic patients.